Biodistribution of the saponin-based adjuvant Matrix-M™ following intramuscular injection in mice - Carnrot, Cecilia; Carow, Berit; Palm, Anna-Karin E.; Akpinar, Eray; Helgesson, Per-Henrik; Osterman, Ingrid Lekberg; Bringeland, Emelie; Foreman, Bryant; Patel, Nita; Bankefors, Johan; Fries, Louis; Stertman, Linda (Frontiers in Drug Delivery, 2023)
Novel adjuvants are extensively utilized in the development of safe and effective vaccines against emerging pathogens. Matrix-M™ adjuvant is a saponin-based adjuvant used in several active clinical development programs and in widespread use in the COVID-19 vaccine NVX-CoV2373.Here, we conducted a biodistribution study to better understand the mechanism of action and safety profile for Matrix-M™ adjuvant. Radiolabeled saponins or cholesterol were incorporated into Matrix-A™ particles, which represent 85% of Matrix-M™. Labeled Matrix-M™ adjuvant was given to mice by intramuscular injection with or without SARS-CoV-2 Spike protein. Radioactivity of the adjuvant components was quantified in local and systemic tissues at seven timepoints over a period of 1-168 hours.The highest saponin levels were found at the 1-hour timepoint at the injection site, in the draining (iliac) lymph nodes, and in urine. Saponins were rapidly cleared from these tissues, reaching very low levels by 48-72 hours. Systemically, saponins were found at low levels in the plasma, kidneys, liver, and bone marrow, and were barely detectable in other investigated tissues. Cholesterol was also found at high levels at the injection site and in the draining lymph nodes. These levels declined rapidly at first, then plateaued at 24-48 hours. Radiolabeled cholesterol was found at very low levels in other tissues at the earliest timepoints, until increasing and stabilizing after the 24-hour timepoint, indicating entry into the endogenous cholesterol recycling pool.This study demonstrates a rapid distribution of Matrix-M™ adjuvant from the injection site to the draining lymph nodes, thus excluding a depot effect as central to the mechanism of action for this adjuvant. The diverging clearance patterns for saponins and cholesterol are suggestive of at least partial disassembly of the Matrix-particles, which has implications for the downstream effects of Matrix-M™ adjuvant on adaptive immune responses. Systemic exposure to toxicologically relevant tissues is very low.